1982
DOI: 10.3109/02844318209006588
|View full text |Cite
|
Sign up to set email alerts
|

Results from Resection of the Distal end of the Ulna After Fractures of the Lower end of the Radius

Abstract: Pain, impaired mobility and weakness in the wrist are common complications after fractures of the lower end of the radius. When these symptoms persist, resection of the distal end of the ulna has been the surgical treatment of choice. 24 patients who had undergone this procedure were reviewed. 50% stated they were not improved by the operation. Of 11 patients with degenerative changes in the distal radio-ulnar joint on preoperative X-ray, 8 stated they were helped by the operation, while of 13 patients without… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0
7

Year Published

1989
1989
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(24 citation statements)
references
References 7 publications
0
17
0
7
Order By: Relevance
“…4 Except for a single large distal fragment, fracture fixation of the ulna in this area is technically difficult, 5 and although Ring et al 6 have demonstrated success with larger fragments, the authors have not found a satisfactory means for returning stability while recreating normal congruous articular anatomy. 4,7 Late problems of degenerative arthritis with ulna-sided wrist pain and instability are not infrequent after failure to restore normal anatomy. 4,8Y10 These late ulna-sided wrist problems may be secondary to healing of the radius in a foreshortened position creating positive ulnar variance with an ulnocarpal abutment syndrome, incongruity of the distal radioulnar joint providing loss of normal rotational mechanics through the distal radioulnar joint, or loss of the normal suspensory mechanics of the TFCC and its ligamentous attachments.…”
mentioning
confidence: 99%
“…4 Except for a single large distal fragment, fracture fixation of the ulna in this area is technically difficult, 5 and although Ring et al 6 have demonstrated success with larger fragments, the authors have not found a satisfactory means for returning stability while recreating normal congruous articular anatomy. 4,7 Late problems of degenerative arthritis with ulna-sided wrist pain and instability are not infrequent after failure to restore normal anatomy. 4,8Y10 These late ulna-sided wrist problems may be secondary to healing of the radius in a foreshortened position creating positive ulnar variance with an ulnocarpal abutment syndrome, incongruity of the distal radioulnar joint providing loss of normal rotational mechanics through the distal radioulnar joint, or loss of the normal suspensory mechanics of the TFCC and its ligamentous attachments.…”
mentioning
confidence: 99%
“…"Rettungseingriffe" entwickelt. Af Ekenstam et al [2] berichteten in einer Studie mit 24 Patienten in 50% der Fälle nach einer DarrachResektion über eine ausbleibende Besserung der Schmerzen und eine verminderte Griffkraft. Bell et al [3] berichteten 1985 über das sog.…”
Section: Diskussionunclassified
“…Overall improvement of forearm rotation, grip strength and pain has been reported following each of these procedures. The remaining reduction of grip strength [5,6], the high incidence of painful instability of the distal end of the ulna [7,8] and possible secondary extensor tendon ruptures [9,10] following complete resection of the ulnar head have lead to the advise to limit this procedure only to the treatment of rheumatoid patients [8,11,12]. However, these complications may occur in patients with rheumatoid arthritis as well.…”
Section: Introductionmentioning
confidence: 97%